PENGARUH SUASANA TOKO, PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI MALL BAYWALK PLUIT JAKARTA - Aminuddin Tambunan; Bonifasius MH Nainggolan (Human Capital Development, 2023)
The purpose of this research is to determine the role of store atmosphere, promotions and service quality in increasing consumer satisfaction at Baywalk Pluit Mall, Jakarta. This research uses a quantitative approach in the form of a survey, with 100 consumers. Purposive sampling was used to identify respondents by distributing questionnaires to consumers who had visited more than once. Instrument measurement using a Likert scale refers to research variables and indicators. Data analysis uses multiple linear regression analysis with the help of SPSS 26 software. Research findings show that store atmosphere has a positive and significant effect on consumer satisfaction, the same thing happens with promotions and service quality. These results also show that the combination of the three variables significantly influences consumer satisfaction. Of the three variables studied, promotion is the most dominant factor influencing satisfaction, next is shop atmosphere and last is service quality. The three variables, namely atmosphere, promotion and service quality have a significant simultaneous effect on consumer satisfaction at the same time.